Performance Improvement Strategies for Vendor Managed Inventory (VMI) to Support the Three Pillars of Higher Education: A Case Study at Institut Teknologi Bandung - Atty Aryanti Saraswati; Hery Suliantoro; Diana Puspita Sari (Green Publisher Indonesia, 2026)
Vendor Managed Inventory (VMI) is a strategic approach in inventory management that enhances supply chain efficiency and integration. In higher education institutions, the availability of office supplies, paper, and printer ink is essential to ensure the smooth implementation of education, research, and community service activities. However, studies evaluating the implementation of VMI in Indonesian higher education institutions remain limited.This study aims to evaluate the performance of the VMI system implemented at Institut Teknologi Bandung (ITB) and formulate strategies to improve VMI performance in order to strengthen its support for the implementation of the Three Pillars of Higher Education. The research employed a mixed-methods approach, consisting of a quantitative survey of 32 work units and qualitative analysis through open-ended responses and in-depth interviews with vendors, VMI administrators, and the Directorate of Logistics. The analysis includes validity and reliability tests, descriptive statistics, gap analysis, thematic coding, triangulation, SWOT–TOWS analysis, and prioritization of strategies using the QSPM method. The results show that VMI significantly improves procurement efficiency, item availability, and data transparency. However, gaps remain in system integration, catalog completeness, and SLA compliance particularly for printer ink. The SWOT–TOWS and QSPM analyses produced four priority strategies: system integration and SLA monitoring; improvement of catalog quality; implementation of early-warning mechanisms and buffer stock; and development of SOPs for risk mitigation and multi-vendor options. Study concludes that strengthening and developing VMI in structured manner has direct impact on the operational sustainability of ITB and significantly supports the implementation of the Three Pillars of Higher Education.